The Effect of Low Temperature Test on Lubrication Performance of Palm Kernel Oil with Addition of PPD as A Lubricant (ASTM D4172) / Aiman. Y and Syahrullail. S - Y, Aiman; S, Syahrullail (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper present a case studies to highlights the importance of renewable and sustainable material to develop a bio lubricant. A research has been done to study the low temperature performance and to investigate the low temperature tribological performance of the palm kernel oil with addition of different percentage PPD (5w%, 10wt%, 20wt% and 30wt %) according ASTM D4172. The main analysis that been done in this research are low temperature performance ability of blended PKO, coefficient of friction (COF), wear scar diameter (WSD), surface roughness and surface profile. The result of the experiment show that for low temperature performance, PKO with 20wt%PPD (A2-20%) and 30wt%PPD (A2-30%) show great performance which can withstand lower temperature (15℃). Under low temperature test tribological performance the coefficient of friction (COF) is increase as the starting temperature is lower with A2-30% has the highest COF. For wear scar diameter it can see that palm kernel oil having high wear scar compare to A2-5%, A2-10%, A2-20% and A2-30%, the trend shows that adding PPD successful improve the lubricity performance in terms of wear scar diameter. The low starting temperature slightly has effect the lubricity performance in terms of surface roughness. At 75˚C the surface roughness is decreasing from A2-5% to A2-20%. Abrasive wear was the dominant wear mechanism for all sample at all starting temperature and a few adhesive wear were spotted at all test.